Risk of Relapse in Patients With Ulcerative Colitis With Persistent Endoscopic Healing: A Durable Treatment Endpoint - Jangi, Sushrut (J Crohns Colitis, 2020)
BACKGROUND: Deep remission in patients with UC has relied on initial achievement of biochemical, endoscopic, and/or histological remission. We evaluated persistent symptomatic remission and endoscopic healing (EH: Mayo endoscopy score [MES] 0 or 1) on consecutive endoscopic examinations as a durable treatment endpoint. METHODS: In a retrospective cohort study, we estimated and compared cumulative risk of clinical relapse in patients with persistent EH, with and without persistent histological remission and depth of EH, among adults with active UC treated-to-target of symptomatic remission and EH who achieved and maintained symptomatic remission and EH over two serial endoscopic assessments. We also explored risk of relapse in patients with persistent EH whose therapy was de-escalated. RESULTS: Of 270 patients who initially achieved EH with treatment-to-target, 89 maintained symptomatic remission and EH on follow-up endoscopy [interval between EH1 and EH2, 16 months]. On follow-up after EH2 [median, 19 months], 1-year cumulative risk of relapse in patients with persistent EH was 11.5%, and with persistent histological remission was 9.5%. Seventeen patients with persistent EH, who underwent de-escalation of therapy, did not have an increased risk of relapse as compared with patients who continued index therapy [5.3% vs 14%, p = 0.16]. CONCLUSIONS: Patients with active UC treated-to-target of clinical remission, who achieve and maintain symptomatic remission and EH over consecutive endoscopies, have a low risk of relapse, particularly in a subset of patients who simultaneously achieve histological remission. Persistent EH should be examined as a treatment endpoint suggestive of deep remission.